Study on the Allocation and Development of Tourism Resources in Sanya - Wenbo Lyu; Jiajun Yin; Zhennan Wang; Minqi Zheng; Yuxin Wang (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
Sanya, located in the southernmost part of Hainan Island, is a famous tropical coastal tourism city in our country. In the past 30 years, since the establishment of the provincial special economic zone, Sanya has rapidly grown from a small border town to a tourism and leisure resort with a high reputation and reputation. This paper began with the resource allocation and development of Sanya’s tourism industry to discuss the development status quo of Sanya’s tourism industry, the existing problems and the corresponding liberation plan.